Observatório da formação docente continuada para coleta de dados sobre necessidades formativas - Barbosa, Cristiane Clébia (2021)
The teacher training process needs to happen permanently, but the offer of courses must reflect the specific and contextual needs of the different realities faced by teachers. Identifying the training demands must be a process that precedes the planning of the courses since the knowledge of such elements can bring a diagnosis and effectiveness to a training contextualized with the reality of the teachers. Thus, this research aims to create an Observatory of Continuing Teacher Education (ObFoCo), to contribute to training institutions in proposing courses with themes more in tune with the reality of the school floor. ObFoCo is a system for collecting teacher training demands to support the provision of continuing education courses. The methodological path of this work had the following specific objectives: a) To discover how teachers send their training needs to training institutions; b) Analyze how the proposal for continuing teacher training courses by the training institutions takes place, and c) Develop a permanent data collection system on teachers' training demands. The scientific method used for this work was Design Science Research (DSR), with a qualitative and applied approach. The research is also exploratory and descriptive. The investigative field was defined in public and private schools in the State of Rio Grande do Norte-RN. The number of respondents to the survey was 215 teachers and six representatives of training institutions. Most of the teachers declared that they were not consulted about their training needs and, in addition to the training proposed by the institutions they work for, seek training on their own. The participating training institutions reported that they did not have a system to collect training demands. ObFoCo was developed as an Information System (IS). The training needs registered by the teachers will be the input data and the output will be the list of training demands divided by type of knowledge: Pedagogical, Content, and Technological. At ObFoCo, teachers are the protagonists of your training, constantly updating the system with information about your training needs. The training institutions will have a database with specific training demands presented by the teachers.